1990
DOI: 10.1007/bf00016503
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of phytochrome mRNA abundance by red light and benzyladenine in etiolated cucumber cotyledons

Abstract: Northern blot analysis revealed that a single 4.2 kb phytochrome mRNA species was detectable in cotyledons excised from five-day-old etiolated cucumber seedlings. Intact etiolated five-day-old cucumber seedlings were given a red light or benzyladenine treatment, and cotyledons were harvested at various times following treatment. The abundance of phytochrome mRNA in the cotyledons was quantitated using 32P-labeled RNA probes and slot blot analysis. By 2 h after irradiation the phytochrome mRNA level was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…The size of the band was estimated to be 4.2 kb, consistent with previous estimates (5,9). The regions of little phy probe hybridization in the low mol wt smear correspond to the positions of the 18S and 25S ribosomal RNAs (Figs.…”
Section: Isolation Of Rna and Blot Analysessupporting
confidence: 88%
See 2 more Smart Citations
“…The size of the band was estimated to be 4.2 kb, consistent with previous estimates (5,9). The regions of little phy probe hybridization in the low mol wt smear correspond to the positions of the 18S and 25S ribosomal RNAs (Figs.…”
Section: Isolation Of Rna and Blot Analysessupporting
confidence: 88%
“…High stringency washes of blots hybridized with a probe that is likely to be poorly conserved between type I-encoding and other phy mRNAs suggest that it is type I-encoding phy mRNA that reaccumulates during exposure to CWL. Although type I-encoding phy mRNA has been previously demonstrated to reaccumulate during darkness after a red light pulse (2,5), no previous data have shown that phy mRNA Analyses of cab mRNA induction and rRNA in total RNA could reaccumulate to substantial levels during a CWL treatom cucumber cotyledons. A, RNA blot analysis of CWLment.…”
Section: Evidence That Type I-encoding Phytochrome Mrna Reaccumulatesmentioning
confidence: 95%
See 1 more Smart Citation
“…The transcription of numerous chloroplastic genes is induced by light and CKs (Cohen et al 1988;Bracale et al 1988). Benzyl-adenine inhibits the transcription of the PHYA gene (Cotton et al 1990), as does light. The synthesis of isopentenyl-adenosine is induced by R, an effect reversed by FR (Qamaruddin & Tillberg 1989).…”
Section: Light and Cytokininsmentioning
confidence: 99%
“…Polysomal RNA was isolated as described by Byrne et al (1993). RNA gel blots, hybridization with antisense RNA probes, and liquid scintillation spectroscopy were performed as previously reported (Cotton et al, 1990;Seeley et al, 1992).…”
Section: Rna Lsolation and Analyslsmentioning
confidence: 99%